FINANCIAL PERFORMANCE, SHARIA SUPERVISORY BOARD, AND CORPORATE GOVERNANCE AND ITS IMPACT ON SOCIAL RESPONSIBILITY AT INDONESIAN SHARIA BANK - NILA PRATIWI; TONNY YUWANDA; ABDI FADHLAN; SHINTA BELLA (Maqdis: Jurnal Kajian Ekonomi Islam, 2022)
This study aims to find out how much influence the financial performance, sharia supervisory board, and corporate governance on sharia banking responsibilities in Indonesia. The population in this study is all Sharia banks in Indonesia from 2015 to 2019. In contrast, the samples in this study were determined by purposive sampling, so 14 samples were obtained. The type of data used is secondary data obtained from www.bi.go.id. Based on the results of financial performance research, it does not influence social responsibility, the sharia supervisory board does not affect social responsibility, and partially there is a positive and significant influence between corporate governance on Islamic social responsibility in sharia banking in the period 2015-2019.